2022
DOI: 10.1002/cne.25314
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptors in a songbird brain

Abstract: Nicotinic acetylcholine receptors (nAChRs) are ligand-gated ion channels that mediate fast synaptic transmission and cell signaling, which contribute to learning, memory, and the execution of motor skills. Birdsong is a complex learned motor skill in songbirds. Although the existence of 15 nAChR subunits has been predicted in the avian genome, their expression patterns and potential contributions to song learning and production have not been comprehensively investigated. Here, we cloned all the 15 nAChR subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
3
6
0
Order By: Relevance
“…To this end, we conducted single-nuclei RNA sequencing (snRNA-seq) from the basal ganglia nucleus Area X and the cortical vocal output nucleus RA of F1 hybrids (n = 6 birds for each) at the subsong stage. In agreement with previous reports in zebra finches [53][54][55] , we identified the genetic signatures that matched multiple cell types reported for the song nuclei, such as Area X medium spiny neurons (MSNs), Area X pallidal-like neurons, RA glutamatergic projecting neurons, GABAergic neurons, astrocytes, microglia, oligodendrocytes, and oligo precursor cells (OPC) (Fig. 5A).…”
Section: Neural Transcriptional Characteristics In the Vocal Motor Nu...supporting
confidence: 91%
See 1 more Smart Citation
“…To this end, we conducted single-nuclei RNA sequencing (snRNA-seq) from the basal ganglia nucleus Area X and the cortical vocal output nucleus RA of F1 hybrids (n = 6 birds for each) at the subsong stage. In agreement with previous reports in zebra finches [53][54][55] , we identified the genetic signatures that matched multiple cell types reported for the song nuclei, such as Area X medium spiny neurons (MSNs), Area X pallidal-like neurons, RA glutamatergic projecting neurons, GABAergic neurons, astrocytes, microglia, oligodendrocytes, and oligo precursor cells (OPC) (Fig. 5A).…”
Section: Neural Transcriptional Characteristics In the Vocal Motor Nu...supporting
confidence: 91%
“…Subclusters in glutamatergic neurons in RA were identified based on a previous report 53,54 and in situ hybridization database, ZEBrA 87 ; SRD5A2 and SCUBE1 for the glutamatergic neurons in RA projecting to the nucleus of cranial nerve XII; CACNA1H, MGAT4C, and ADYAP1 for RA surrounding arcopallial neurons. Unknown clusters with no specific marker gene and several small clusters (less than 60 cells in each) were filtered out.…”
Section: Cell Cluster Analysismentioning
confidence: 99%
“…In agreement with previous reports in ZFs [60][61][62], we identi ed marker genes representing speci c cell types reported for the song nuclei, such as Area X medium spiny neurons (MSNs), Area X pallidal-like neurons, RA glutamatergic projecting neurons, GABAergic neurons, astrocytes, microglia, oligodendrocytes, oligo precursor cells, and RA surrouding arcopallium glutamatergic neurons (Fig. 5A).…”
Section: Transcriptional Characteristics In Neurons In the Vocal-moto...supporting
confidence: 88%
“…Subclusters in MSNs and pallidal-like neurons were identi ed with FOXP2, FOXP4, MTNR1A, and PENK based on a previous report [62]. Subclusters in glutamatergic neurons in RA were identi ed based on a previous report [60,61] and in situ hybridization database, ZEBrA [96]; SRD5A2 and SCUBE1 for the glutamatergic neurons in RA projecting to the nucleus of cranial nerve XII; CACNA1H, MGAT4C, and ADYAP1 for RA surrounding arcopallial neurons. Unknown clusters with no speci c marker gene and several small clusters (less than 60 cells in each) were ltered out.…”
Section: Cell Cluster Analysismentioning
confidence: 99%
“…We also found multiple acetylcholine genes upregulated in high-singing starlings, including choline O-acetyltransferase (CHAT), a choline transporter (SLC5A7), and a muscarinic cholinergic receptor (CHRM4). Multiple immunolabeling studies have shown high concentrations of cholinergic proteins in the song control system in the zebra finch brain [57][58][59], and cholinergic stimulation of the HVC via carbachol modulates zebra finch song [60]. However, the literature regarding its role in brain regions involved in social behavior is limited.…”
Section: Neurotransmitter Systems Previously Implicated In Social Beh...mentioning
confidence: 99%